PERAN GURU AGAMA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DENGAN KETERBATASAN SARANA PRASARANA (STUDI KASUS SD NEGERI BATUJAYA III KARAWANG) - Atsmanih Nurilahi; Nadjematul Faizah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2025)
Limited infrastructure in Islamic Religious Education (PAI) learning, which can affect the effectiveness of the teaching and learning process. This study aims to determine the roles of Religious Education Teachers, Principals, and School Committees in Islamic Religious Education (PAI) learning with limited infrastructure at Batujaya III Elementary School, Karawang. This study uses a qualitative approach with descriptive methods. The research results show that religious teachers have made efforts in teaching Islamic Religious Education (PAI) despite limited infrastructure, with the support of the principal and school committee. Therefore, collaboration between all parties is a crucial factor in maintaining the continuity and quality of PAI learning.